How to utilize FDI to improve transport infrastructure - roads : lessons from Australia and Peru - Allan, Rory...[et al.] (UN New YorkUS, 2009)
Describes and analyzes the policies and approaches of two countries with experience in private sector solutions to improving roads infrastructure.